Macroeconomics / edited by Prabhat Patnaik - Patnaik, Prabhat (ed.) (New Delhi, 1999)
This collection of essays deals with macroeconomic issues relating to the Indian economy. It locates discussions on India within the general literature on macroeconomics, and critically surveys this literature. It is intended for senior undergraduates and postgraduates, teachers and economists.
Keywords: Macroeconomic